Lighting the Wick: Four Perspectives on the Role of Mediators (2018)
Conversation with four antioquia mediators: Cristina Buitrago, Lina Guisao, Monica Sepúlveda and Andrey Palacio each with a different approach and through their experience agree that the role of the mediator is not of redeemer but of giving a community the desire to learn and sometimes the tools for that learning